THE IMPACT OF SELF-EFFICACY AND SELF ESTEEM ON INTERNSHIP STUDENTS JOB PERFORMANCE - Runtukahu, Archelia Lara Gabriele; Saerang, David Paul Elia; Pandowo, Merinda Herrari Ch. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
With education evolving beyond academic learning, universities recognize experiential learning, one of which is exposing students to an internship program as it is critical to boost the graduates’ employability. Shortcomings and limitations of the internship program affect students’ performance, while universities and companies have certain expectations, students’ will have to rely on their self-core for great internship job performance. This study aims to understand how their self-core of Self-Efficacy and Self-Esteem impacts their Internship Job Performance. The research approach is using a quantitative approach, using an online questionnaire targeted at Management students from Faculty of Economics and Business Sam Ratulangi University who took an internship as a compulsory course in the period of 2022/2023. Probability sampling was used to select a sample of 70 respondents among the population. The analysis results indicate that Self-Efficacy has no influence on Internship Job Performance, meanwhile Self-Esteem has a positive influence on Internship Job Performance. Simultaneously, Self-Efficacy and Self-Esteem has a positive influence on Internship Job Performance.   Keyword: Self-Efficacy, Self-Esteem, Internship Job Performance